Asthma epidemiology in Brazil, from 2016 to 2020 (Research, Society and Development, 2022)
Asthma is a chronic inflammation of the lower airways, triggered by allergic factors in the external environment, in which an interaction between genetic and external factors is observed, leading to hyperresponsiveness of these airways, due to light. It affects, in the world, about 334,000 people. This study aims to study the epidemiology of asthma in Brazil. Therefore, an epidemiological, descriptive study of secondary data from DATASUS (Ministry of Health), from 2016 to 2020, collected in 2021, was carried out. The results are tabulated. Excel and statistically analyzed not Bioestat 5.3. I note that there is a significant reduction in the number of hospitalizations for asthma in Brazil in 2020, in all regions. The Northeast region was the region with the highest number of internationals. In relation to gender: since women had a slightly higher number of hospitalizations for this pathology; Age group: 1 to 4 years represents 31.28% of internationals, the brown race represents 45.91%, expenditures are quite expressive in all regions. The number of deaths was 2,248 cases in 05 years, the highest number of deaths in the Southeast Region. Although there was a significant reduction in the number of hospitalizations, or in the accumulated number of deaths, in the period, as well as in the number of hospitalizations, it inspires us to a careful observation of asthma, realizing that it is necessary not to administer this disease.